The Progressive Legal Perspective of Legal Justice in Customary Dispute Resolution Related to Natural Resources - Muhammad Akbar; Maisa; Mohamad Didi Permana; Mohd Hazmi Mohd Rusli (Magister of Law, Faculty of Law, Universitas Mataram., 2024)
Indexed by Scopus